Development of a stand-alone and scalable weather monitoring system using two-way vhf radios - Maria Lynn B. Carbonell; John Michael R. Carpio; Juan Carlo C. Medina; John Paul Perote; Tristian Jhan J. Tamayo; Gerino P. Mappatao (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
As weather-related disasters visit the Philippines regularly and the intensity increases over time, an all-weather system of monitoring the weather and its effects is necessary. Specifically, when super typhoon Yolanda (with international name Haiyan) devastated central Philippines in 2013, almost all public terrestrial communication systems were down. This paper proposes a “back-to-the-basics”, stand-alone and scalable system used to monitor the weather in several locations. The system is not dependent on the public telecommunication systems but rather uses the old but reliable very high frequency (VHF) two-way communication system for the transmission of sensor data such as temperature, wind speed and direction, rainwater precipitation and water level. The scalability feature of the system allows the addition of more monitoring stations to cover a wider area. Based on the tests conducted with the prototype composed of a command center and three (3) local monitoring stations, the system was able to demonstrate the transmission of weather data as well as the scalability feature of the system. The system is envisaged that the proposed system can be very useful in weather monitoring in a provincial setting where the command center is in the provincial capitol and the monitoring stations are in municipalities and cities within the province.